2002
DOI: 10.1002/ccd.10106
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional analysis of cyclic changes in coronary artery shape

Abstract: The objective of this study was to derive a method for quantifying the dynamic geometry of coronary arteries. Coronary artery geometry plays an important role in atherosclerosis. Coronary artery geometry also influences the performance of coronary interventions. Conversely, implantation of stents may alter coronary artery geometry. Clinical tools to define vessel shape have not been readily available. Using a Frenet-Serret curvature analysis applied to 3D reconstruction data derived from standard coronary angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…For the coronary artery, curvature range of the LAD in this study was within those reported in previous studies 13,23,28 although individual anatomic variation along the length would have a greater effect on the numerical values. We also observed a greater curvature change in the distal LAD than the proximal portion which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…For the coronary artery, curvature range of the LAD in this study was within those reported in previous studies 13,23,28 although individual anatomic variation along the length would have a greater effect on the numerical values. We also observed a greater curvature change in the distal LAD than the proximal portion which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 76%
“…According to this formula, curvature and torsion are defined as j ¼ a 0 Â a 00 k k= a 0 k k 3 and s ¼ ða 0 Â a 00 Þ Á a 000 = a 0 Â a 00 k k 2 , respectively, where a indicates a position vector in space. 9,28,29,33,35,53 By definition, this curvature metric measures an infinitesimal rate of change in the tangent vector at each point of the curve, whereas the torsion metric measures the infinitesimal rate of change in the orientation (binormal vector of the curve) of the osculating plane. While curvature is well appreciated because of its reciprocal relation to the radius of curvature, the torsion metric is less frequently used in practice because of its susceptibility to error in calculations associated with higher-order derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The cyclic change in coronary artery shape not only alters coronary artery curvature but also produces discrete flexion points. 9 Another unique feature of coronary arteries is that phasic pressure and blood flow are not synchronous as the maximum pressure is in systole and most coronary blood flow occurs during diastole (although there are rare exceptions). [10][11][12] This unique relationship is responsible for a highly negative stress phase angle between coronary artery circumferential strain and wall shear.…”
Section: Mechanical Deformation Of Coronary Arteriesmentioning
confidence: 99%
“…In three-dimensional analysis tortuosity of the artery is best described by the well-known Frenet formulas which define the tortuosity of the spatial curve (arterial centerline) through its curvature and torsion [11,[23][24][25]. The Frenet frame is formed by three vectors: tangent, normal, and binormal that form the orthonormal basis.…”
Section: -2 / Vol 134 June 2012mentioning
confidence: 99%